A new partial transmit sequence scheme using genetic algorithm for peak-to-average power ratio reduction in a multi-carrier code division multiple access wireless system. (6th April 2009) - Zhang, Yang; Ni, Qiang; Chen, Hsiao-Hwa
One major drawback of multi-carrier broadband wireless transmission system is that its signal may cause high peak-to-average power ratio (PAPR). This article proposes a new partial transmit sequence (PTS) scheme using genetic algorithm for PAPR reduction in a synchronous multi-carrier code division multiple access wireless system. We investigate the impact of each genetic algorithm operator and optimally configure genetic algorithm to be suitable for the practical system design. The simulation results demonstrate that our proposed genetic algorithm-based PTS scheme achieves low PAPR values with much lower computational complexity than other existing solutions. Meanwhile, the optimal parameters of genetic algorithm assisted PTS are provided.